AKTIVITAS TABIR SURYA FRAKSI METANOL DARI DAUN SIMPUR (Dillenia indica Linn.) DAN KARAKTERISASI SENYAWA ISOLATNYA - Salatiana Salatiana; Endah Sayekti; Gusrizal Gusrizal (Tanjungpura University, 2023)
Sunscreen activity has been tested on simpur leaves (Dillenia indica Linn.) by determining the value of sun protection factor (SPF), erythema transmission percentage (%Te) and pigmentation transmission percentage (%Tp) of each methanol extract, n-hexane, dichloromethane fraction, and methanol fraction from simpur leaves. This test was carried out using a UV-Vis spectrophotometer (λ = 200-400 nm), a variation of sample concentration of 50; 75 and 100 ppm. The methanol fraction at a concentration of 100 ppm showed the highest SPF value of 4.630 ± 0.043 and the lowest %Te and %Tp values of 32.316 ± 0.297 and 52.699 ± 0.160, respectively. Isolation of flavonoids from the methanol fraction produced a relatively pure isolate (Rf = 0.901) with code G1 in the form of a yellowish-green solid/powder (1.5 mg). Characterization of isolate G1 using the FTIR spectrophotometer showed that there were vibrations of the alcohol O-H groups (3446.79 cm-1), aliphatic C-H (2958.80-2858.51 cm-1), C=C aromatic (1635.64 cm-1), C=C aromatic (1635.64 cm-1), C =O (1730.15 cm-1), C-O alcohol (1122.57 cm-1), and aliphatic C-H (1463.97-1382.96 cm-1). Based on a comparison of the spectra of isolate G1 with the spectra from the literature, isolate G1 was predicted as a flavonoid compound in the flavan or flavanol groups